An Analysis of Ideological Square on Joe Biden and Vladimir Putin Speech Related to Russia-Ukraine War - Kauthsar, Abhid Al; Hamzah, Hamzah (English Language and Literature, 2024)
Critical Discourse Analysis studies of communication in political contexts have scrutinized the use of language by politicians striving to win public opinion related to some topic or conflict. utilizing Teun A. van Dijk's framework for political discourse analysis, this thesis examines discursive devices and ideological squares in four speeches related to the Russia Ukraine conflict in 2022 from president Joe Biden and president Vladimir Putin. The study described in this thesis combines micro-level text analysis focusing on discursive devices and macro-level analysis focusing on the ideology formed by the ideological square that represents "us" and "them within it. the data analysis explains the discursive devices that only the president uses Biden namely "disclaimer" "euphemism" "national self-glorification" "number game" and "polarization", on the other hand discursive devices that are only found in president Putin namely "authority" and "comparison". in using ideological square president Biden uses " de-emphasizing negative "us" more than president Putin and on the other hand president Putin uses "emphasizing negative "them" and "de-emphasizing positive "them" more. The results of the study also show that the two presidents conveyed different ideological perspectives and attitudes on the 2022 Ukraine and Russia conflict based on the four speeches analysed.